Peran Kadaster Kelautan pada Penyelenggaraan Integrated Coastal Zone Management (ICZM) dalam Rangka Pembangunan Berkelanjutan di Indonesia - Gathan Rasendriya Khumar; Eka Djunarsjah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The distribution of the Indonesian population that tends to occupy coastal areas is a challenge to the governance system in the region. Environmental, ecosystem, disaster, economic, and land use problems are the focus of coastal area management solutions. Therefore, coastal management is needed that focuses on various problems, especially the environment, to ensure sustainable development in Indonesia. The concept of marine cadastre focuses on the 3R aspect (right, restriction, responsibility) in terms of marine space governance and will then play a major role in the concept of integrated coastal area management or Integrated Coastal Zone Management (ICZM). In the concept of the UN Ocean Decade, marine cadastre can support the achievement of a healthy, resilient, productive, and sustainable sea. A healthy sea means that the sea must be kept clean and unpolluted, resilient means making the sea a strong space for tourism activities and transportation of goods/services, while productive is interpreted as encouraging all activities at sea to generate economic value. This study will analyze the role of marine cadastre in various aspects of ICZM so that coastal management can be implemented optimally. The general orientation of various aspects of coastal management will also prioritize various sustainable development goals.